2014
DOI: 10.1093/jxb/eru373
|View full text |Cite
|
Sign up to set email alerts
|

Comparative physiological, metabolomic, and transcriptomic analyses reveal mechanisms of improved abiotic stress resistance in bermudagrass [Cynodon dactylon (L). Pers.] by exogenous melatonin

Abstract: SummaryExogenous melatonin application confers abiotic stress resistance in bermudagrass through modulation of antioxidants and metabolic homeostasis, and extensive transcriptional reprogramming such as the reorientation of photorespiratory, carbohydrate, and nitrogen metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

38
396
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 455 publications
(447 citation statements)
references
References 85 publications
38
396
1
Order By: Relevance
“…MEL has been shown to differentially regulate expression of genes associated with the antioxidant enzymes including ascorbate-glutathione, auxin-related genes, development-associated genes and senescence-associated genes in plant cells 106,107,127,132 . Recent differential expression analyses of transcriptomes of plants exposed to MEL have found that the expression of more than 1300 genes are modified by MEL in A. thaliana and over 300 in cucumber.…”
Section: Melatonin and 5ht In Flowering Reproduction And Chronoregulmentioning
confidence: 99%
See 1 more Smart Citation
“…MEL has been shown to differentially regulate expression of genes associated with the antioxidant enzymes including ascorbate-glutathione, auxin-related genes, development-associated genes and senescence-associated genes in plant cells 106,107,127,132 . Recent differential expression analyses of transcriptomes of plants exposed to MEL have found that the expression of more than 1300 genes are modified by MEL in A. thaliana and over 300 in cucumber.…”
Section: Melatonin and 5ht In Flowering Reproduction And Chronoregulmentioning
confidence: 99%
“…This adds a further level of complexity to the signaling networks influenced by MEL 59,127,156 . Furthermore specific research has started to uncover the mechanisms behind this regulation with a Crepeat-binding factors (CBFs)/drought response element binding 1 factors (DREB1s) as well as WRKY, MYB and bHLH transcription factors being implicated in mediation of these responses 48,132,157 . Though large-scale transcriptomics analysis has not been …”
Section: Melatonin and 5ht In Flowering Reproduction And Chronoregulmentioning
confidence: 99%
“…[1][2][3] Exogenous application of small molecules could effectively alleviate damages caused by multiple abiotic stresses, including drought, salt and cold. [4][5][6][7][8] Exogenous ABA treatment improved drought stress tolerance in 'TifEagle' cultivar through induction of H 2 O 2 and NO, which, in turn, enhanced antioxidant enzyme activities. 4 Our studies indicated that exogenous CaCl 2 , polyamines, H 2 S, and NO treatments were effective to induce bermudagrass tolerance to drought, salt, and cold stresses.…”
mentioning
confidence: 99%
“…17 More recently, high throughput RNA seq analysis showed that exogenous melatonin treatment conferred improved salt, drought, and cold stress tolerances in bermudagrass through modulation of 3933 genes (2361 up-regulated and 1572 downregulated). 7 Melatonin (N-acetyl-5-methoxytryptamine) is a well-known animal hormone which is also found to play important roles in plant development and abiotic stress responses. [18][19] Exogenous melatonin treatment alleviated ROS burst and cell damage induced by abiotic stress in bermudagrass.…”
mentioning
confidence: 99%
See 1 more Smart Citation